2017
DOI: 10.18203/2394-6040.ijcmph20173832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different phenotypic methods for the detection of methicillin resistant Staphylococcus aureus and antimicrobial susceptibility pattern of MRSA

Abstract: Background: Rapid and accurate detection of methicillin resistant Staphylococcus aureus (MRSA) is an important role of clinical microbiology laboratories to avoid treatment failure. The aim of this study was to compare conventional methods against the cefoxitin disc diffusion method to determine the best phenotypic method. Methods: Study was carried out in the Department of Microbiology, National Institute of Medical Sciences & Research, Jaipur (India), between July 2016 – December 2016. The methods includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
3
8
0
Order By: Relevance
“…92.31% of MRSA isolates were found sensitive to clindamycin which corresponds to the findings of Arjyal et al (2020) [22] who reported 100% sensitivity of MRSA isolates towards clindamycin. In line with present observation Selvabai et al (2017) [20] , Sharma et al (2017) [28] , Li et al (2017) [27] , Ahmad et al (2015) [19] , Al-Zaidi and Al-Sulami (2013) [15] and Kumar et al, (2011) [33] reported fairly similar rate of sesnistivity towards clindamycin. Whereas higher rate of resistance towards clindamycin was reported by Krishnan et al (2019) [21] , Sohail and Latif (2018) [34] and Goyal et al (2013) [24] .…”
Section: Antibiogram Of Mrsasupporting
confidence: 86%
See 1 more Smart Citation
“…92.31% of MRSA isolates were found sensitive to clindamycin which corresponds to the findings of Arjyal et al (2020) [22] who reported 100% sensitivity of MRSA isolates towards clindamycin. In line with present observation Selvabai et al (2017) [20] , Sharma et al (2017) [28] , Li et al (2017) [27] , Ahmad et al (2015) [19] , Al-Zaidi and Al-Sulami (2013) [15] and Kumar et al, (2011) [33] reported fairly similar rate of sesnistivity towards clindamycin. Whereas higher rate of resistance towards clindamycin was reported by Krishnan et al (2019) [21] , Sohail and Latif (2018) [34] and Goyal et al (2013) [24] .…”
Section: Antibiogram Of Mrsasupporting
confidence: 86%
“…Existance of vancomycin resistant MRSA during present study was well supported by Shah et al (2019) [18] , Nasution et al (2018) [17] and Al-Zaidi and Al-Sulami (2013) [15] . In contrast, Mahmood et al (2010) [23] , Selvabai et al (2017) [20] , Sonth et al (2015) [26] , Li et al (2017) [27] , Sharma et al (2017) [28] and Krishnan et al (2019) [21] reported 100% sensitivity of MRSA to vancomycin. Vancomycin, a glycopeptide antibiotic usually remains a drug of choice for treatment of MRSA infections.…”
Section: Antibiogram Of Mrsamentioning
confidence: 99%
“…Similarly, susceptibility testing using cefoxitin, a stronger inducer of the mecA regulatory system than oxacillin that is used to detect methicillin resistance 42 , failed to accurately identify OS-MRSA (Table 1). These observations suggest that a combination of oxacillin and cefoxitin susceptibility tests, as recommended elsewhere 43 , or detection of mecA will be more reliable for the identification of MRSA. Despite being phenotypically susceptible to oxacillin, β-lactam resistance can easily be induced in OS-MRSA 20,21,44 .…”
Section: Discussionmentioning
confidence: 64%
“…The MIC lesser than or equal to 2 microgram was considered sensitive and and greater than or equal to 4 microgram was considered resistant. 17…”
Section: E-strip Methodsmentioning
confidence: 99%